PENGARUH EXPERIENTIAL MARKETING DAN KEPERCAYAAN TERHADAP LOYALITAS KONSUMEN PENGGUNA MARKETPLACE SHOPEE DI KOTA BEKASI - Hendayana, Yayan; Solichati, Ummy (Program Studi Pendidikan Manajemen Perkantoran, 2021)
This study aims to determine the influence of marketing and trust on consumer loyalty to Shopee marketplace users in Bekasi City. The sample used in this study were 165 respondents using Shopee in Bekasi City, but only 154 respondents who met the requirements and could be analyzed further. Testing in this study uses Structural Equation Modeling (SEM) with the AMOS program. The results show a high Goodness of Fit and simultaneous and individual testing also provides significant results. The results of data analysis show that experiential marketing and trust from users of the Shopee marketplace in Bekasi City have a positive and significant effect on consumer loyalty.